2023
DOI: 10.1038/s41598-023-33078-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic, kinetic, and isotherm studies of Direct Blue 86 dye absorption by cellulose hydrogel

Abstract: In this study, cellulose hydrogels were simply fabricated by the chemical dissolution method using LiCl/dimethylacetamide as a new method, and the hydrogel produced was investigated for removing Direct Blue 86 (DB86) dye from the aquatic environment. The produced cellulose hydrogel (CAH) was characterized by FTIR, XRD, SEM, and TGA analyses. The removal efficiency of DB86 dye using CAH was achieved via a batch equilibrium process. The impact of pH, time of contact, CAH dosage, starting concentration of DB86 dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Thus, it is evident that the initial concentration of the MB dye was crucial for its adsorption from its water solution. Shoaib et al 74 observed a similar pattern in their study on the adsorption of the dye Direct Blue 86. When MB dye molecules adhere to the DPKB-S adsorbent, they are first…”
Section: Effect Of Initial Mb Dye Concentrationmentioning
confidence: 54%
“…Thus, it is evident that the initial concentration of the MB dye was crucial for its adsorption from its water solution. Shoaib et al 74 observed a similar pattern in their study on the adsorption of the dye Direct Blue 86. When MB dye molecules adhere to the DPKB-S adsorbent, they are first…”
Section: Effect Of Initial Mb Dye Concentrationmentioning
confidence: 54%
“…Four common isotherm models, namely, Langmuir [22] (Equation ( 4)), Freundlich [23] (Equation ( 6)), Dubinin-Radushkevich (D-R) [24] (Equation ( 7)), and Temkin [25] (Equation ( 10)), were applied to the experimental data.…”
Section: Isotherm Studymentioning
confidence: 99%